Gas Metal Arc Welding of Thermo-Mechanically Controlled Processed S960MC Steel Thin Sheets with Different Welding Parameters - Michal Jambor; Frantisek Novy; Milos Mician; Libor Trsko; Otakar Bokuvka; Filip Pastorek; Daniel Harmaniak (Communications - Scientific letters of the University of Zilina, 2018)
In this paper are presented results of mechanical properties evaluation of the thin sheets welds made of the S960MC TMCP steel, which were executed using the GMAW procedure with different process parameters. The microstructural changes in the heat affected zone (HAZ) were evaluated, as well. The microstructural observation revealed significant changes in the HAZ and the three main zones, coarse grain, fine grain and intercritical (CGHAZ, FGHAZ and ICHAZ) were identified in the HAZ for both sets of tested welding parameters. Evaluation of the micro-hardness showed significant reduction of the micro-hardness in the ICHAZ, for both tested states, and the ICHAZ was identified as the most critical area of the whole welded joint. Results of the tensile tests revealed significant reduction of mechanical properties regardless of the welding parameters.